The Importance of Collocational Awareness To Learners of English in Translation - Gede Eka Putrawan (Universitas Lampung, 2015)
Translation is a bridge to connect two different cultures by the conversion of linguistic system, a medium that enables people to interact well with others coming from different cultural and linguistic backgrounds. To make a translated text more natural, acceptable, and readable, the awareness and mastery of collocations should be taken into account. A translator should understand that this word, for example, collocates with that word or that word always comes with this word. A student of English or a translator should be aware of this situation when translating, for example, from Indonesian into English or vice versa, that the translated text sounds natural to native speakers of English. Therefore, in translating a text, especially from Indonesian into English, collocations play an important role. If we do not increase our collocational awareness in English, it is quite hard to produce native-like expressions in the target language, English. The hardest part when we deal with translation is on how to make readers become unaware that they are reading a translated text.Key words: English, collocations, translation, translated text